Socialization of Tax Obligations for MSMEs in Sudimara Pinang Village - Eni Suharti; Hamdani; Ikhfi Imaniah; Ranti Imaniar (Jurnal Pengabdian Masyarakat Bestari, 2023)
This community service activity has the aim of increasing tax literacy, increasing awareness of taxpayers' tax obligations, helping taxpayers to be able to calculate the amount of tax owed by MSMEs in the Sudimara Pinang sub-district area, Ciledug sub-district, Tangerang city. This socialization was carried out offline in the Sudimara Pinang sub-district hall. . As a result of this activity, the majority of MSME actors still have a low level of tax literacy, resulting in a low level of compliance with their tax obligations.